How does climate change adaptation policy in India consider gender? An analysis of 28 state action plans. (9th August 2021) - Singh, Chandni; Solomon, Divya; Rao, Nitya
ABSTRACT: Gender mediates climate vulnerability and adaptation action. Consequently, climate change adaptation policy has seen a push towards 'mainstreaming' gender and prioritizing 'gender-responsive' climate action. However, it is unclear to what extent this mainstreaming advances or obscures gender considerations and whether current climate policies reflect developments in the gender and climate change literature. This paper explores how gender is operationalized in adaptation policy in India through a policy review of 28 State Action Plans on Climate Change. We juxtapose normative goals around reducing differential vulnerability with policy approaches to mainstreaming gender and propose entry points that link advances in gender and feminist studies with climate change adaptation policy. Our analysis indicates that most subnational climate policies in India explicitly mention gender as a mediator of vulnerability and adaptive capacity but operationalize it inadequately and unevenly. We also reflect on how the heuristics of mainstreaming get operationalized in policies (gender-blind, gender-sensitive, to gender-transformative approaches) and what that means for addressing gendered vulnerability. Key policy insights While explicitly mentioned, gender concerns are unevenly operationalized in India's subnational climate policy. In most State Action Plans on Climate Change in India, gaps exist between normative goals such as reducing differential vulnerability and empowering women, and policy approaches (namely gender-blind, -neutral, -specific, -sensitive, and -transformative approaches). To be effective, the conceptualization of gender must expand beyond focussing on differences between women and men to engaging more with intersections of sex, caste, class, and resources.